Distribution and malignancy risk of six categories of the pathology reporting system for thyroid core-needle biopsy in 1,216 consecutive thyroid nodules - Son, Hye Min (Ultrasonography, 2020)
PURPOSE: The purpose of this study was to present the distribution of lesions among the six categories of the pathology reporting system for thyroid core-needle biopsy (CNB), along with the range of malignancy risk of each category based on different diagnostic criteria for benignity in a clinical cohort. METHODS: For 1,216 consecutive nodules (≥1 cm) of 1,125 patients who underwent CNB at two hospitals, the diagnostic results based on the six categories of thyroid CNB were analyzed. Patients were divided into three groups according to prior fine-needle aspiration (FNA) status: second-line CNB for nodules where prior FNA yielded nondiagnostic or unsatisfactory results (n=57), second-line CNB for nodules with prior FNA results of atypia/follicular lesion of undetermined significance (AUS/FLUS) (n=303), and first-line CNB (n=856). RESULTS: The proportion of nodules in each CNB category and the range of the malignancy rate for each category was as follows, in order from category I to VI: 1.8%, 23.1%-75.0%; 57.9%, 0.7%-16.7%; 16.0%, 13.2%-46.7%; 8.8%, 53.8%-56.8%; 2.0%, 100%; and 13.5%, 100%. First-line CNB was associated with a higher rate of conclusive diagnoses (category II, IV, or VI) (725 of 856, 84.7%) than second-line CNB with prior nondiagnostic or AUS/FLUS FNA results (241 of 360, 66.9%; P<0.001). CONCLUSION: The overall distribution of nodules across the six categories of thyroid CNB and the ranges of malignancy risk for those categories were presented in a clinical cohort. First-line CNB tended to produce a higher rate of conclusive results than second-line CNB with prior inconclusive FNA results.